Health and Environmental Hazards of Electronic Waste in India. - Borthakur, Anwesha (Journal of Environmental Health, 2016)
Technological waste in the form of electronic waste (e-waste) is a threat to all countries. E-waste impacts health and the environment by entering the food chain in the form of chemical toxicants and exposing the population to deleterious chemicals, mainly in the form of polycyclic aromatic hydrocarbons and persistent organic pollutants. This special report tries to trace the environmental and health implications of e-waste in India. The author concludes that detrimental health and environmental consequences are associated with e-waste and the challenge lies in producing affordable electronics with minimum chemical toxicants.